A critical review on steps applied to conduct activities in reading classes to improve students’ vocabulary development and expand vocabulary use - Mariann Edwina Mariadass,; Mohd Hasrul bin Kamarulzaman,; Yokana Veliapandian, (Penerbit Universiti Kebangsaan Malaysia, 2022)
A majority of people consider intense reading as a great strategy to improve competence in vocabulary and language skills. However, educators believe that the time commitment required to use the intensive reading technique is a major barrier to its adoption. In order to teach students about short stories, novels, poems, and other types of creative writing, literature professors frequently use the intense reading method. The value of the intensive reading technique is a topic of much investigation. This study compared reading to intensive reading and considered how the two could be integrated. The primary objective of this study is to determine whether the Intensive Reading Method works well for teaching new vocabulary words utilizing its suggested procedures. In order to explore the intensive reading approach to improve language proficiency in writing, reading comprehension, and vocabulary, a systematic literature review was used. The results showed that the procedures taken in 70% of the studies were acknowledged as essential for carrying out the intensive reading approach. The Intensive Reading Method was employed in 14 out of 20 research studies, and it was proven to be successful in assisting learners in acquiring new vocabulary.